Presepsi Wajib Pajak Tentang Pendapatan, Kesadaran, Pengetahuan Pajak dan Kemudahan Layanan terhadap Kepatuhan Wajib Pajak dalam Membayar PBB di Kelurahan Joglo Kecamatan Banjarsari Kota Surakarta - Aida Rahmawati Dwi Kencana; Bambang Widarno, (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This study is to test and analyze taxpayers' perceptions of income, awareness, tax knowledge and ease of service on taxpayers' compliance in paying land and building taxes in Joglo Village, Banjarsari District, Surakarta City. This study uses the slovin formula so that the sample obtained by 96 respondents However, after the classical assumption test, namely the heteroscedasticity test and the normality test, are not significant or are said to have not passed the test, so the researcher must use outlier data and the respondent data is reduced by 3 to be declared passed. So the number of samples used in this study is 93. The data collection technique uses a questionnaire. The analysis techniques used were Descriptive Analysis, Validity Test, Reality Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-Test, F Test and Coefficient of Determination. This study shows the results that taxpayers' income does not have a significant effect on taxpayers' compliance in paying land and building taxes, taxpayers' awareness does not have a significant effect on taxpayers' compliance in paying land and building taxes, Tax knowledge has a significant effect on taxpayer compliance in paying land and building taxes, ease of service does not have a significant effect on taxpayer compliance in paying land and building taxes